2014
DOI: 10.1017/s1751731114000676
|View full text |Cite
|
Sign up to set email alerts
|

Determination of non-market values to inform conservation strategies for the threatened Alistana–Sanabresa cattle breed

Abstract: Livestock breed-related public good functions are often used to justify support for endangered breed conservation despite the fact that little is known about such non-market values. We show how stated preference techniques can be used to assess the nonmarket values that people place on livestock breeds. Through the application of a case study choice experiment survey in Zamora province, Spain, the total economic value (TEV) of the threatened Alistana-Sanabresa (AS) cattle breed was investigated. An analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…They are also common in environmental economics where they are commonly employed to place a dollar value on environmental and public goods. The method has been widely applied in wildlife [ 45 , 46 ] and domestic animal conservation [ 47 , 48 ]. Recently they have been applied to explore preferences among flagship species [ 3 5 , 19 ], including birds [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…They are also common in environmental economics where they are commonly employed to place a dollar value on environmental and public goods. The method has been widely applied in wildlife [ 45 , 46 ] and domestic animal conservation [ 47 , 48 ]. Recently they have been applied to explore preferences among flagship species [ 3 5 , 19 ], including birds [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In terms of ecosystem services science, for formal acceptance of livestock biodiversity as a cultural ecosystem service, the beneficiaries need to be identified and valuations made of the service (Braat & de Groot, ). Examples of this having been achieved in livestock biodiversity include the study of Martin‐Collado, Diaz, Drucker, Carabaño, and Zander () of Alista‐Sanabresa cattle. In this case, non‐market values (defined in terms of willingness to pay for such benefits as maintenance of local rural culture and increased certainty of the breed's future existence) account for 80% of total economic value.…”
Section: Livestock Biodiversity and Ecosystem Services Sciencementioning
confidence: 99%
“…Zander et al (2013) and Martin-Collado et al (2014) showed that in the case of threatend European livestock breeds, livestock systems have significant public value in generating resource diversity. Livestock systems can also connect habitats through the dispersal of seeds across geographies, enabling the movement of plant species in response to the changing climate (Hoffmann et al, 2014).…”
Section: Supporting and Habitat Servicesmentioning
confidence: 99%